2018
DOI: 10.1126/sciadv.aar5319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures and functional analysis of beige adipocytes induced from in vivo intra-abdominal adipocytes

Abstract: Bat and mouse beige adipocytes induced from white adipocytes provide insights into therapy against obesity-related disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Compared with Ctrl-Adi, Suc-Adi are enriched with genes associated with beige adipocytes, although less in the representative genes related to white adipocytes (Fig. 6B) (30)(31)(32). Accordingly, pathway enrichment analysis demonstrated that the PI3K-Akt pathway and the AMPK pathway were altered in adipocytes differentiated from ADSCs with succinate treatment, further supporting succinate-treated ADSCs with a strong preference to generate beige adipocytes (SI Appendix, Fig.…”
Section: Robust Mitochondrial Complex II Activity In Scd1-deficient Adscsmentioning
confidence: 71%
“…Compared with Ctrl-Adi, Suc-Adi are enriched with genes associated with beige adipocytes, although less in the representative genes related to white adipocytes (Fig. 6B) (30)(31)(32). Accordingly, pathway enrichment analysis demonstrated that the PI3K-Akt pathway and the AMPK pathway were altered in adipocytes differentiated from ADSCs with succinate treatment, further supporting succinate-treated ADSCs with a strong preference to generate beige adipocytes (SI Appendix, Fig.…”
Section: Robust Mitochondrial Complex II Activity In Scd1-deficient Adscsmentioning
confidence: 71%
“…Besides, H&E staining revealed significantly smaller adipocytes size in the E2F1 –/– WAT compared with WT WAT, which presented “beige” adipose-like morphology. As Xue et al reported that after exposure to cold temperatures, subcutaneous WAT of mice possessed relatively large, round, and condensed mitochondria with numerous transverse cristae surrounding smaller lipid droplets, indicating browning of WAT ( Xue et al, 2018 ). Here, E2F1 –/– WAT showed smaller intracellular lipid droplets and more mitochondria quantities than WT WAT, revealing the beige adipose shape.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed a previously unrecognized role of LETM1 in obesity-related hypertension by acting as a mitochondrial Ca 2+ modulator in BAT. In addition, LETM1 is also required for the browning of WAT to form beige adipocytes, indicating a promotional effect of LETM1 in the maintenance of BAT [ 33 ]. In our study, we observed that the knockout of TRPV1 directly upregulated the expression of both UCP1 and LETM1, suggesting that TRPV1 is involved in controlling the normal activity of BAT, which might be related to its regulatory effect on sympathetic nerves, as the activation of TRPV1 in the nucleus tractus solitarius has been reported to inhibit BAT sympathetic nerve activity and decrease BAT metabolism [ 34 ].…”
Section: Discussionmentioning
confidence: 99%